Atención al cliente en la Cooperativa de Ahorro y Crédito Coac Credil Limitada en el cantón Salcedo periodo 2022-2023. - Inlago Cabascango, Jasmin Dayana (2023)
This research report studies the internal and external customer service at the COAC CREDIL Saving and Credit Limited Cooperative in Salcedo canton. The general objective is to present a tool that helps to improve service and customer service. So, the researcher has used the servqual model as a reference, which will allow measuring the quality of service through expectations and perceptions of clients in five dimensions that are improved according to the need of the users. Analytical type investigation was used since the shortcomings that appear in the organization will be observed, giving solutions to all the concerns that may be generated when providing customer service; subsequently, the implementation of a mailbox of complaints and claims has been taken into account as a proposal to create better care for all users who are part of the organization. Therefore, the researcher can conclude that customer service must constantly be changing through the application of strategies that help to improve the shortcomings generated during the cooperative's existence, offering quality service at all times to meet the expectations that the client wishes.